Prolonging the lifetime of wireless sensor networks by cross-layer interaction. - Van Hoesel, L. (IEEE Wireless communications)
This article presents a cross-layered approach for networking in wireless sensor networks. WSNs differ greatly from traditional ad hoc wireless networks and therefore require the use of new types of network protocols that are energy-efficient to ensure a node lifetime of several years on a single battery and can operate without assistance of central managers in a dynamic network topology. We show that a tightly integrated set of networking protocols is a good solution to reach the target of highly energy-efficient WSNs. Our approach combines medium access organization with routing.